2013
DOI: 10.1007/s00259-013-2431-x
|View full text |Cite
|
Sign up to set email alerts
|

Improved quantification of small hearts for gated myocardial perfusion imaging

Abstract: PurposeIn patients with a small heart, defined as an end-systolic volume (ESV) of ≤20 mL calculated using the Quantitative Gated SPECT (QGS) program, underestimation of ESV and overestimation of ejection fraction (EF) using gated myocardial perfusion imaging are considered errors caused by inappropriate delineation of the left ventricle (LV). The aim of this study was to develop a new method for delineation of the LV and to evaluate it in studies using a digital phantom, normal subjects and patients.MethodsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 21 publications
(25 reference statements)
4
39
0
1
Order By: Relevance
“…LV delineation in diastole using IQ-SPECT underestimates EDV and resulted in decreased LVEF. The relatively higher frequency of small hearts in this study population might be one of the factors [28]. The finding of this study suggested that this technical problem requires further investigation [28][29].…”
Section: Functional Analysismentioning
confidence: 62%
“…LV delineation in diastole using IQ-SPECT underestimates EDV and resulted in decreased LVEF. The relatively higher frequency of small hearts in this study population might be one of the factors [28]. The finding of this study suggested that this technical problem requires further investigation [28][29].…”
Section: Functional Analysismentioning
confidence: 62%
“…However, it is hard to explain why were ESV values so small (even zero) in some patients in our study. Nakajima et al 16 compared EF, EDV and ESV values of patients with small hearts, using QGS and EXINI programs, with that of a digital phantom and with the data analysis results of the Japanese Society of Nuclear Medicine (JSNM) group, performed in 2007. The main outcome of the study was that the EF values calculated by the QGS program were found to be higher than those calculated by the EXINI program.…”
Section: Discussionmentioning
confidence: 99%
“…The shift is inversely proportional to the measured midventricular LV cavity volume, ranging from 3.5 mm at 0 mL (effectively ''guessing'' a cavity where one cannot be seen) to 0 mm at 85 mL, where spillover is deemed to have abated (see Figure 1 and Ref. 12).…”
Section: See Related Article Pp 1378-1388mentioning
confidence: 99%